The Gaṇitatilaka and its commentary - Petrocchi, Alessandra, author.
1 online resource.
Keywords: "The Gaṇitatilaka and its commentary : two Medieval Sanskrit mathematical texts, presents the first English annotated translation and analysis of the Gaṇitatilaka Sripati and its Sanskrit commentary by the Jaina monk Simhatilakasuri (13th century CE). Simhatilakasuri's commentary upon the Gaṇitatilaka is a key text for the study of Sanskrit mathematical jargon and a precious source of information on mathematical practices of Medieval India; this is, in fact, the first known Sanskrit mathematical commentary written by a Jaina monk, upon whom we have substantial information, to survive to the present day. In presenting the first annotated translation of these two Sanskrit mathematical texts, this volume focuses on language in mathematics, and put forward a novel, fresh approach to Sanskrit mathematical literature which favors attention to linguistic, literary features, and textual data. This key resource makes these important texts available in English for the first time for students of ancient and medieval mathematics. This key resource makes these important texts available in English for the first time for students of Sanskrit, medieval mathematics, South Asian history, and philology."--